An emergy-based hybrid method for assessing industrial symbiosis of an industrial park. (15th February 2016) - Zhe, Liu; Yong, Geng; Hung-Suck, Park; Huijuan, Dong; Liang, Dong; Tsuyoshi, Fujita
Abstract: Industrial park development has become a critical strategy to promote economic development in many countries since 1980s. Particularly, China is one key country to adopt such a method on enhancing its industrialization. However, rapid industrial park development has resulted in many issues, including resource depletion, environmental emissions and pressure on responding climate change. Industrial symbiosis has been proved that it has positive impacts on promoting resource utilization efficiency. Therefore, effective performance evaluation can help recognize the key barriers on industrial symbiosis of industrial parks so that more appropriate policies can be raised by considering the local realities. Emergy synthesis is one feasible method on addressing the contribution of local ecosystem to industrial park development due to its innovative perspectives and mature methodology, while impact, population, affluence, technology (IPAT) formula and index decomposition analysis (IDA) are suitable for identifying and quantitatively calculating the key impacts of various factors. This paper integrated emergy synthesis, IPAT formula and IDA methods together to investigate the impact factors of industrial symbiosis in an industrial park. A case study approach at Dalian Economic Development Area (DEDA) was carried out so that such an effort can be tested. The results show that waste reutilization by industrial symbiosis in DEDA increased by 3.0E+20 seJ from 2006 to 2010. Technological pressure for waste utilization by industrial symbiosis and energy structure of an industrial park had made negative effects on the waste reutilization from 2006 to 2010 in DEDA, while the efficiency of non-renewable energy consumption and emergy scale of an industrial park played positive effects on the waste reutilization. Among the four impact factors, technological pressure for waste utilization and the efficiency of non-renewable energy consumption took more significant impacts on the industrial symbiosis of DEDA than the other two factors, which contributed −1.92E+21 seJ and 2.18E+21 seJ for the waste reutilization by industrial symbiosis respectively.